Integrative Analysis of Vaginal Microorganisms and Serum Metabolomics in Rats With Estrous Cycle Disorder Induced by Long-Term Heat Exposure Based on 16S rDNA Gene Sequencing and LC/MS-Based Metabolomics - An, GaiHong; Zhang, Yu; Fan, LiJun; Chen, JiaJun; Wei, MengFan; Li, Chao; Chen, XueWei; Zhang, Li; Yang, DanFeng; Wang, Jing (Frontiers in Cellular and Infection Microbiology, 2021)
Long-term heat exposure (HE) leads to estrous cycle disorder (ECD) in female rats and damages reproductive function. However, the regulation mechanism of vaginal microorganisms and serum metabolomics remains unclear. This study aimed to explore the effects of microbes on vaginal secretions of rats with ECD and describe the characteristics of serum metabolomics and their relationship with vaginal microorganisms. The alterations in the serum levels of neurotransmitters were used to verify the possible regulatory pathways. The relative abundance, composition, and colony interaction network of microorganisms in the vaginal secretions of rats with ECD changed significantly. The metabolomics analysis identified 22 potential biomarkers in the serum, which were mainly involved in lipid metabolism, amino acid metabolism, and mammalian target of rapamycin and gonadotropin-releasing hormone (GnRH) signaling pathways. Further, 52 pairs of vaginal microbiota–serum metabolites significantly correlated (21 positively correlated and 31 negatively correlated). Gardnerella positively correlated with the metabolite L-arginine and negatively correlated with oleic acid, Pseudomonas negatively correlated with L-arginine，while the metabolite benzoic acid negatively correlated with Adlercreutzia. These four pairs of bacteria–metabolites had a direct or indirect relationship with the estrous cycle and reproduction. The levels of glutamine, glutamate, and dopamine were significantly uncontrolled. The former two were closely related to GnRH signaling pathways, which might be involved in the development and regulation of heat exposure (HE)-induced ECD in rats. Serum neurotransmitters partly reflected the regulatory effect of vaginal microorganisms on the host of HE-induced ECD, and glutamatergic neurotransmitters might be closely related to the alteration in vaginal microorganisms. The findings might help comprehend the mechanism of HE-induced ECD and build the foundation for proposing a new intervention based on vaginal microorganisms.